Respuesta :
Answer:
Step-by-step explanation:
(fg)(x) )
[tex](x+4)*(3x^{2} -7)[/tex]=[tex]3x^{3} -7x+12x^{2} -28[/tex] = [tex]3x^{3} +12x^{2} -7x-28[/tex]
Composite functions are functions that are gotten from combining multiple functions.
The value of the composite function (f o g)(x) is 3x^2 -3.
The functions are given as:
[tex]f(x) = x + 4[/tex]
[tex]g(x) = 3x^2 - 7[/tex]
To calculate the composite function (f o g)(x), we make use of:
[tex](f\ o\ g)(x) = f(g(x))[/tex]
We have:
[tex]f(x) = x + 4[/tex]
Substitute g(x) for x
[tex]f(g(x)) = g(x) + 4[/tex]
Substitute [tex]g(x) = 3x^2 - 7[/tex]
[tex]f(g(x)) = 3x^2 - 7 + 4[/tex]
[tex]f(g(x)) = 3x^2 -3[/tex]
Recall that:
[tex](f\ o\ g)(x) = f(g(x))[/tex]
So, we have:
[tex](f\ o\ g)(x) = 3x^2 -3[/tex]
Hence, the value of the composite function (f o g)(x) is 3x^2 -3.
Read more about composite functions at:
https://brainly.com/question/10687170